Use of Whole-Genome Sequencing of Adenovirus in Immunocompromised Pediatric Patients to Identify Nosocomial Transmission and Mixed-Genotype Infection. (4th June 2018) - Houldcroft, Charlotte J; Roy, Sunando; Morfopoulou, Sofia; Margetts, Ben K; Depledge, Daniel P; Cudini, Juliana; Shah, Divya; Brown, Julianne R; Romero, Erika Yara; Williams, Rachel; Cloutman-Green, Elaine; Rao, Kanchan; et al.
Abstract : This study used whole-genome sequencing directly from clinical samples to analyze adenovirus from immunocompromised pediatric patients. We identified one nosocomial transmission event, which included cases that occurred 4 years apart and 1 case of mixed-genotype adenoviremia. Abstract: Background: Adenoviruses are significant pathogens for the immunocompromised, arising from primary infection or reinfection. Serotyping is insufficient to support nosocomial transmission investigations. We investigate whether whole-genome sequencing (WGS) provides clinically relevant information on transmission among patients in a pediatric tertiary hospital. Methods: We developed a target-enriched adenovirus WGS technique for clinical samples and retrospectively sequenced 107 adenovirus-positive residual diagnostic samples, including viremias (>5 × 10 4 copies/mL), from 37 patients collected January 2011–March 2016. Whole-genome sequencing was used to determine genotype and for phylogenetic analysis. Results: Adenovirus sequences were recovered from 105 of 107 samples. Full genome sequences were recovered from all 20 nonspecies C samples and from 36 of 85 species C viruses, with partial genome sequences recovered from the rest. Whole-genome phylogenetic analysis suggested linkage of 3 genotype A31 cases and uncovered an unsuspected epidemiological link to an A31 infection first detected on the same ward 4 years earlier. In 9 samples from 1 patient who died, we identified a mixed genotype adenovirus infection. Conclusions: Adenovirus WGS from clinical samples is possible and useful for genotyping and molecular epidemiology. Whole-genome sequencing identified likely nosocomial transmission with greater resolution than conventional genotyping and distinguished between adenovirus disease due to single or multiple genotypes.